Rapid Shifts in Visible Carolina Grasshopper (Dissosteira carolina) Coloration During Flights - Martin, Ezekiel; Steinmetz, Henry L.; Baek, Seo Young; Gilbert, Frederick R.; Brandley, Nicholas C. (Frontiers in Ecology and Evolution, 2022)
Some brightly colored structures are only visible when organisms are moving, such as parts of wings that are only visible in flight. For example, the primarily brown Carolina grasshopper (Dissosteira carolina) has contrasting black-and-cream hindwings that appear suddenly when it takes off, then oscillate unpredictably throughout the main flight before disappearing rapidly upon landing. However, the temporal dynamics of hindwing coloration in motion have not previously been investigated, particularly for animals that differ from humans in their temporal vision. To examine how quickly this coloration appears to a variety of nonhuman observers, we took high-speed videos of D. carolina flights in the field. For each of the best-quality takeoffs and landings, we performed a frame-by-frame analysis on how the relative sizes of the different-colored body parts changed over time. We found that in the first 7.6 ± 1.5 ms of takeoff, the hindwings unfurled to encompass 50% of the visible grasshopper, causing it to roughly double in size. During the main flight, the hindwings transitioned 6.4 ± 0.4 times per second between pauses and periods of active wing-beating (31.4 ± 0.5 Hz), creating an unstable, confusing image. Finally, during landings, the hindwings disappeared in 11.3 ± 3.0 ms, shrinking the grasshopper to 69 ± 9% of its main flight size. Notably, these takeoffs and landings occurred faster than most recorded species are able to sample images, which suggests that they would be near-instantaneous to a variety of different viewers. We therefore suggest that D. carolina uses its hindwings to initially startle predators (deimatic defense) and then confuse them and disrupt their search images (protean defense) before rapidly returning to crypsis.